Electrified methane reforming decarbonises methanol synthesis. (April 2022) - Mion, Anna; Galli, Federico; Mocellin, Paolo; Guffanti, Simone; Pauletto, Gianluca
Abstract: Power-to-X processes convert free electrons stemming from renewable energy into chemical bonds. In this framework, electrochemical processes drastically increase energy demand. Differently, directly electrified thermochemical processes, such as electrically heated methane reforming, minimise renewable energy requirements and achieve high decarbonisation levels. In the case of electrically heated methane reforming carbon dioxide emission from the stuck of the firebox is avoided. In this work, we report two innovative process configurations for methanol production that involve an electrically heated methane reformer for syngas generation. Reforming of methane and carbon dioxide containing gas streams into syngas coupled with methanol synthesis can achieve negative carbon dioxide balance without requiring carbon capture and sequestration. Increasing the amount of reformed carbon dioxide, it is possible to increase its consumption. Integration of an electrolyser is required when syngas with a hydrogen/carbon monoxide below 2 is generated. It results that the integration of an electrically heated reformer in a methanol plant makes it possible to convert respectively 0.3 t and 0.93 t of carbon dioxide per ton of methanol produced. The consumption of renewable electricity is 2.3 MWh and 7.1 MWh per ton of methanol produced. Highlights: Direct electrification of methane reformer. Steam and dry reforming in methanol plants. Electrified reformer integration in methanol plants. Integration of an electrolyser with an electrically heated methane reformer.